Advanced glycation end-products inhibitors isolated from Schisandra grandiflora. Issue 4 (16th February 2016) - Poornima, B.; Anand Kumar, D.; Siva, Bandi; Venkanna, A.; Vadaparthi, P.R. Rao; Kumar, K.; Tiwari, Ashok K.; Suresh Babu, K.
Abstract : Free radicals scavenging and advanced glycation end-products (AGEs) inhibitory potentials in crude chloroform extract of Schisandra grandiflora were evaluated. Bioassay-guided isolation of the chloroform extract led to the identification of 24 compounds. Among the isolates, ( ± ) gomisin M1, arisantetralone C and D, macelignan, saurulignan B and SZ-MO displayed potent-free radical scavenging as well as AGEs inhibitory potentials. This is the first report identifying the presence of AGEs inhibitory activity and assigning AGEs inhibitory activity to these compounds. Therefore, our research finds new application of traditional medicinal plant S. grandiflora having capacity to reduce formation and accumulation of AGEs in diabetes. Abstract :